Imidazo[1,2-a]pyridine-appended chalcone and Schiff base conjugates: Synthetic, spectrophotometric, biological, and computational aspects - Seema R. Jadhav; Shailesh S. Gurav; Haya Yasin; Promila Nagpal; Suraj N. Mali (Chemical Physics Impact)
Herein we describe 2-chloroimidazo[1,2-a]pyridine-appended Schiff base and chalcone conjugates, exploring their synthetic, spectrophotometric, biological, and computational aspects. UV–visible study revealed that scaffolds VIc and VIIIa exhibit bathochromic and hypsochromic shifts respectively compared to their analogs, due to auxochrome effect. The molecular docking simulations were performed to investigate the binding interactions of motifs with three cancerous target proteins (4HJO, 1M14, and 1M17) and four microbial target proteins. The compound VIIIb exhibited significant anti-lung cancer activity (GI50: 22.3) against the A-459 cell line. Moreover, the synthesized compounds exhibited auspicious antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Klebsiella pneumoniae, with MIC ranging from 64 to 175 µg/mL. Additionally, in-silico target prediction analysis suggested a considerable likelihood (26.7%) of acting on kinases for compounds VIIIa and VIIIc. In-silico toxicity scrutiny anticipated all compounds as non-fatal and less toxic as they belong to toxicity class 4 (300 < LD50 ≤ 2000). Further structural insights into the synthesized compounds were gained through optimized geometries, FMOs, MEP plots, and global reactivity descriptors (µ, ɳ, S, and ω), aiding in understanding their structural features, potential reactivity, and toxicity. Overall, these results highlight the potential of the prepared moieties as hopeful intrants for further development.